The use of virtual technologies with music in rehabilitation: a scoping systematic review - Tuominen, Pipsa P. A.; Saarni, Lea A. (Frontiers in Virtual Reality, 2024)
The use of virtual environments in rehabilitation has been growing. The current systematic review aimed to evaluate how and where virtual technologies are combined with music in rehabilitation.A literature search was conducted in seven databases (ACM Digital Library, CINAHL Complete, Cochrane Library, Computer Science database, Medline, Nursing & Allied Health database, and Scopus). It included articles published from 2006 to February 2023. The search followed the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines for study selection. Twelve studies with 160 participants were included in the review. In addition, a descriptive approach was used to gather data from the studies for the areas of interest.Virtual Reality (VR) and Augmented Reality were most familiar and used in rehabilitation, but Mixed Reality, and Extended Reality were less studied. It became evident that equipment, diverse applications, assessment metrics, training environments, and methodologies were highly varied. Most of the studies were pilots, the overall quality of included studies was rated moderate, and the risk of bias was high in the included studies. The studies on motor rehabilitation after stroke showed a clinical improvement in hand functions, specifically fractionation. Furthermore, studies that included motivation, adherence, and mental health, slightly supported the idea that VR technologies with music have the potential to promote motivation and exercise adherence, increase positive emotions, and decrease anxiety. In addition, user experience and feasibility studies presented technologies combined with music to be safe and acceptable in rehabilitation.In light of these findings, it can be inferred that virtual technologies with music offer promising avenues for future rehabilitation research. However, some confusion was obtained related to the included studies' definitions of technologies and management terms. Furthermore, it is important to note the limited number of studies and participants, the heterogeneity among participants, and the overall quality of the studies that restrict the generalizability of these results to a larger population. Therefore, future researchers should define concepts and terms, delve deeper into this area to uncover the potential benefits, and clarify the specific mechanisms through which virtual technologies with music can positively impact rehabilitation outcomes.